Sifat Korosi Dari Material Berbasis Nb yang Mengandung 24% Berat Sn Pada Berbagai Konsentrasi Natrium Klorida [Corrosion Behavior Of Nb-Base Material Containing 24wt% Sn At Various Sodium Chloride Concentrations] - Priyotomo, Gadang (Jurnal Metalurgi, 2015)
The corrosion behavior of Nb-base material containing 24wt% Sn that are consisted of Nb3Sn and NbSn2 phases, has been investigated using polarization test, potentiostatic test and surface analytical method (SEM; scanning electron microscope and EDS; Energy Dispersive Spectroscopy) in neutral NaCl solutions. It was found that the preferential dissolution of NbSn2 phase with a lower Nb concentration compared to Nb3Sn phase. From polarization curves, the corrosion current density and corrosion rate of the material increase with the increase of chloride concentration. In passive region, there is no preferential dissolution in both the phases, whereas the preferential dissolution of NbSn2 takes place in transpassive region. The increase of chloride concentration has detrimental effect in the corrosion resistance of the material. The results obtained were also explained the galvanic effect between the phases generating for the preferential dissolution of NbSn2 phase.